Rural-Urban Migration Pathways and Residential Segregation in the Helsinki Region - Karhula Aleksi; McMullin Patricia; Sutela Elina; Ala-Mantila Sanna; Ruonavaara Hannu (Väestöliitto, 2022)
Migration and residential segregation are intrinsically linked. However, little attention has been given to internal migration and its relationship with socioeconomic segregation. In this study, we illustrate the pathways individuals take between rural and urban settings and examine the association between these pathways and segregation in the Helsinki region. We use register data from Statistics Finland and sequence analysis to illustrate the mobility patterns of two 1980s birth cohorts aged 7 to 37. The majority of Finnish rural-urban pathways are associated with either a childhood spent in an urban area or a move to an urban area in young adulthood. We show that an even larger majority of people living in Helsinki at age 37 spent their childhood there or in other urban environments. We find that internal migrants are positively selected for education and income. A childhood in the outer urban regions of a city reduces the probability of living in low income neighbourhoods when controlling for socioeconomic status and family structure. We found no association between rural childhood and living in poor neighbourhoods.